Pengembangan Game Edukasi Construct 2 pada Pembelajaran Biologi Materi Hormon pada Reproduksi Manusia - Nasikhatul Khusna; Fahrur Rozy (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Educational game learning media provides a systematically arranged digital platform for self-study. These games can effectively complement traditional teaching materials, supporting students' independent learning both at home and outside regular school hours. This researchspecifically aimed to develop a feasible educational game using Construct 2 for Biology Subject on Human Reproduction Hormones, targeting Class XI Science students at MA Al Fatahiyyah.The study employed a Research and Development (R&D) approach, guided by the ADDIE development model (Analyze, Design, Develop, Implement, Evaluate). The content of the developed game media was carefully aligned with the Class XI MA Al Fatahiyyah syllabus,focusing on the "Hormones in Human Reproduction" topic. Research subjects included two media expert lecturers, one biology teacher serving as a material expert, and Class XI students from MAAl Fatahiyyah. Feasibility was assessed using media and material assessment sheets, alongside student response questionnaires. Research findings indicate the developed educational game media is highly feasible for use as a teaching aid. Scores reflected strong approval: 93% from media expert 1, 81% from media expert 2, and 93% from the material expert. Student feedback was also very positive, with 84% from small group testing and 87.89% from large group (field) testing. The overall average percentage reached 86,65%, categorizing the developed educational game learning media as "Very Good." It's concluded that this Construct 2-based educational game on human reproduction hormones is a viable and effective tool to support learning activities for Class XI students at MA Al Fatahiyyah.